Large-grain MBE-grown GaSe on GaAs with a Mexican hat-like valence band dispersion - Chen, Ming-Wei; Kim, Hokwon; Ovchinnikov, Dmitry; Kuc, Agnieszka; Heine, Thomas; Renault, Olivier; Kis, Andras (npj 2D Materials and Applications, 2018)
Atomically thin GaSe has been predicted to have a non-parabolic, Mexican hat-like valence band structure due to the shift of the valence band maximum (VBM) near the Γ point which is expected to give rise to novel, unique properties such as tunable magnetism, high effective mass suppressing direct tunneling in scaled transistors, and an improved thermoelectric figure of merit. However, the synthesis of atomically thin GaSe remains challenging. Here, we report on the growth of atomically thin GaSe by molecular beam epitaxy (MBE) and demonstrate the high quality of the resulting van der Waals epitaxial films. The full valence band structure of nominal bilayer GaSe is revealed by photoemission electron momentum microscopy (k-PEEM), confirming the presence of a distorted valence band near the Γ point. Our results open the way to demonstrating interesting new physical phenomena based on MBE-grown GaSe films and atomically thin monochalcogenides in general.
CRIS-Team Scopus Importer:2022-04-14